Tingkat Kecerdasan Sosial Siswa di SMK Negeri 1 Tanjung Raya - Amelia, Suci Riska; Kamal, Muhiddinur (TSAQOFAH, 2023)
This research is motivated by the fact that there are still students who have poor social intelligence in their social environment. Adolescents' need to be accepted by their environment. Teenagers who can be accepted by the environment are teenagers who have social intelligence. Social intelligence has an important role in supporting student success in the future. Adolescents who fail to develop their social intelligence will experience many obstacles in the social world. As a result, they are easily marginalized socially. The aim of the research is to describe the level of social intelligence of class XI students at SMK Negeri 1 Tanjung Raya. This type of quantitative research is descriptive. The research population was all class XI students at SMK Negeri 1 Tanjung Raya as many as 280 students. The research sample of 70 students was taken using a proportional random sampling technique. Data collection through questionnaires. The results of this research show that in general the level of social intelligence of students in each dimension, namely social sensitivity, social insight, and social communication in the research sample is in the low category with 38 students with a percentage of 54.28%. With an overall average score of 141.5. So, it can be concluded that the level of social intelligence of class XI students at SMK Negeri 1 Tanjung Raya is in the low category. Suggestions for teachers and schools are expected to provide rules that place more emphasis on aspects of students' social intelligence, as an effort to familiarize students in improving their social intelligence. And suggestions for guidance and counseling teachers to facilitate students to develop social skills and solve social problems experienced by students, through providing guidance and counseling services.